OPTIMALISASI POTENSI BUAH MANGROVE Sonneratia alba SEBAGAI DETERJEN CAIR DI PESISIR LHOK BUBON, ACEH BARAT - Selvi Mardalena; Mohamad Gazali; Rina Syafitri; Deri Anggraini; Ropita Ropita; Farah Salsabila; Irnu Alfarisi; Zuriat Zuriat (Universitas Mataram, 2023)
Mangroves are one of the coastal plants that have a high ability to adapt to extreme environments. Mangroves serve as buffer zones in coastal areas with an ecological function capable of dampening Tsunami waves. In addition, mangroves are a source of livelihood for coastal communities, both directly and indirectly. The purpose of implementing this community service program is to provide knowledge and skills to the Lhok Bubon coastal community in West Aceh Regency in making liquid detergent from the Sonneratia alba mangrove. Methods of implementing activities include outreach activities, preparation of raw materials, and training and demonstrations for the Lhok Bubon coastal community. The results of the implementation showed that the coastal community consisting of Lhok Bubon coastal PKK women had a passion for learning and enthusiasm in participating in community service programs. The stages of community service activities carried out include the following (1). Collection of fruit raw materials for S. alba (S. alba) around the coastal area of Lhok Bubon, West Aceh, (2). Conducted trials on the manufacture of S. alba (S. alba) fruit detergent, and training on the manufacture of S. alba fruit liquid detergent (S. alba). The output of this community service activity is an environmentally friendly detergent product. In addition, this PkM activity forms a coastal women's group adjacent to the mangrove forest so that it facilitates the processing of mangroves into environmentally friendly liquid detergent products. Based on the results of community service activities, it can be concluded that the Lhok Bubon coastal community acquired new knowledge and skills in the utilization of S. alba mangrove species as an environmentally friendly liquid detergent.